Criteria Used in Clinical Practice to Guide Immunosuppressive Treatment in Patients with Primary Sclerosing Cholangitis. - Kornelius Schulze; Tobias J Weismüller; Michael Bubenheim; Peter Huebener; Roman Zenouzi; Henrike Lenzen; Christian Rupp; Daniel Gotthardt; Philipp de Leuw; Andreas Teufel; Vincent Zimmer; Florian P Reiter; et al. (PLoS ONE, 2015)
Current guidelines recommend immunosuppressive treatment (IT) in patients with primary sclerosing cholangitis (PSC) and elevated aminotransferase levels more than five times the upper limit of normal and elevated serum IgG-levels above twice the upper limit of normal. Since there is no evidence to support this recommendation, we aimed to assess the criteria that guided clinicians in clinical practice to initiate IT in patients with previously diagnosed PSC.This is a retrospective analysis of 196 PSC patients from seven German hepatology centers, of whom 36 patients had received IT solely for their liver disease during the course of PSC. Analyses were carried out using methods for competing risks.A simplified autoimmune hepatitis (AIH) score >5 (HR of 36, p<0.0001) and a modified histological activity index (mHAI) greater than 3/18 points (HR 3.6, p = 0.0274) were associated with the initiation of IT during the course of PSC. Of note, PSC patients who subsequently received IT differed already at the time of PSC diagnosis from those patients, who did not receive IT during follow-up: they presented with increased levels of IgG (p = 0.004) and more frequently had clinical signs of cirrhosis (p = 0.0002).This is the first study which investigates the parameters associated with IT in patients with PSC in clinical practice. A simplified AIH score >5 and a mHAI score >3, suggesting concomitant features of AIH, influenced the decision to introduce IT during the course of PSC. In German clinical practice, the cutoffs used to guide IT may be lower than recommended by current guidelines.